Attitudes of staff and students towards Vocational Education Program. - Dixon, Kathryn (1991)
The main purpose of this study was to investigate the attitudes of the staff and students at a Western Australian Senior High School towards the Vocational Education program, through examining the factors affecting the development of those attitudes and the factors affecting the implementation of the program. The theoretical base of the study drew on the theories 'of attitude formation proposed by Fishbein (1963) who believed a close relationship between individual belief systems and attitude formation exists.